Detection and significance of neuronal autoantibodies in patients with meningoencephalitis in Vientiane, Lao PDR - Uy, CE; Mayxay, M; Harrison, R; Al-Diwani, A; Jacobson, L; Rattanavong, S; Dubot-Pérès, A; Vongsouvath, M; Davong, V; Chansamouth, V; Phommasone, K; Waters, P; et al. (Oxford University Press, 2022)
Background The importance of autoimmune encephalitis and its overlap with infectious encephalitides are not well investigated in South-East Asia. Methods We report autoantibody testing, using antigen-specific live cell-based assays, in a series of 134 patients (cerebrospinal fluid and sera) and 55 blood donor controls (sera), undergoing lumbar puncture for suspected meningoencephalitis admitted in Vientiane, Lao People's Democratic Republic (PDR). Results Eight of 134 (6%) patients showed detectable serum neuronal autoantibodies, against the N-methyl-D-aspartate and gamma-aminobutyric acid A receptors (NMDAR and GABAAR), and contactin-associated protein-like 2 (CASPR2). Three of eight patients had accompanying autoantibodies in cerebrospinal fluid (two with NMDAR and one with GABAAR antibodies), and in two of these the clinical syndromes were typical of autoimmune encephalitis. Three of the other five patients had proven central nervous system infections, highlighting a complex overlap between diverse infectious and autoimmune causes of encephalitis. No patients in this cohort were treated with immunotherapy, and the outcomes were poor, with improvement observed in a single patient. Conclusions In Lao PDR, autoimmune encephalitis is underdiagnosed and has a poor prognosis. Empiric immunotherapy should be considered after treatable infectious aetiologies are considered unlikely. Awareness and diagnostic testing resources for autoimmune encephalitis should be enhanced in South-East Asia.